Survival of and wheat-root colonization by alginate encapsulated Herbaspirillum spp - el-Komy, H M (Folia microbiologica, 2001)
The survival of Herbaspirillum spp. cells added directly or encapsulated in alginate beads and colonization of wheat roots was evaluated in soil microcosms. Cells entrapped in alginate in the presence of JNFb-broth and introduced into unplanted non-sterile clay loamy and sandy soils survived better than cells added directly to the same soils after 50 d incubation. On amendment by JNFb broth and/or skim milk the entrapped cells survived better than those prepared in water. Encapsulated cells survived better in a heavier textured soil (clay-loamy) than in a lighter (sandy) soil. Wheat plants growing in microcosms inoculated with various bead types from day 0 to day 30 exhibited high levels of histosphere colonization, nitrogenase activity (in situ) measured by acetylene reduction assay, plant dry mass and total N content but no symptoms of mottled stripe disease were observed. Comparable results of growth criteria and nitrogenase activity, but relatively lower bacterial populations, were obtained with wheat grown for 45 d after the inoculant had been introduced into the soil with different bead types.
Keywords: mikrosféry; kultivační média; Betaproteobacteria; algináty; Culture Media; Triticum; půda; Soil; Soil Microbiology; pšenice; kořeny rostlin; Plant Roots; Alginates; Microspheres; půdní mikrobiologie; ekosystém; Ecosystem